Phytochemical Screening of Plants Used in Folkloric Medicine: Effect of Extraction Method and Solvent - Abbas, Mazhar; Shahid, Muhammad; A. Sheikh, Munir; Muhammad, Ghulam (Asian Journal of Chemistry, 2014)
The medicinal plants, Ricinus communis, Croton tiglium and Datura innoxia were screened for phytochemical constituents. The extracting solvents and extraction methods such as shaking, sonication and soxhlet were compared to evaluate their efficiency. The whole plants and plant parts (leaves, stem, root, seed and flower) were extracted with methanol and further fractioned in different solvents. The phytochemical and proximate composition were determined through standard methods. Phytochemical analysis revealed that alkaloids, tannins, saponins, steroids, phlobatannins, flavonoids, terpenoids and C. glycosides were present in the extracts. The quantitative analysis of alkaloids, flavonoids and saponins revealed a considerable variation among plant and parts as well. Furthermore, it was found that extraction method and extracting solvent also affected the phytochemical contents. The moisture, carbohydrate, ash, fat, protein contents and energy value also found to be vary among plants. Results revealed that the plant under investigation have a considerable high amounts of phyto-constituents and a potential sources of new antimicrobial, antioxidant and cytotoxic compounds.